The once and future Bible : an introduction to the Bible for religious progressives - Jenks, Gregory C. (Gregory Charles), 1952- (Eugene, OR : Wipf and Stock Publishers, 2011)
This book offers a way to engage with the Bible as a set of sacred texts that can serve as a song sheet for believers in exile - those people Bishop John Shelby Spong calls the "church alumni association." This includes those internally displaced persons of faith who have not yet become spiritual refugees but who feel the pressure to conform to traditional expressions of faith that no longer serve as springs of living water for the journey of life. These ancient texts come from another world and another time, but they can serve as maps for the journey of life. They can best do this when the sacred wisdom of the Bible is accepted as permission to voice the new questions we face today in the confidence that authentic faith has always required such boldness. Religious progressives are people who live the questions, not dodge them. Our task is not to guard a set of traditional answers, but to live life boldly, taking risks for God's sake and our own. One of the hallmarks of this book is that the problems posed by the Bible are acknowledged. In particular, the contributions of recent critical scholarship are embraced, rather than being ignored or neutralized by pious ambivalence. The intended reader of this book is not a traditional believer, secure in her assumptions about God and salvation, but someone struggling to live with integrity in a time when traditional religion seems increasingly irrelevant. The goal is not to persuade the reader that the Bible is credible but-more modestly-to offer an account of the Bible that may encourage religious progressives to reclaim the Bible as a valued part of our spiritual baggage. -- Publisher.
Pt. 3. Christian texts in the Bible. Prophet of God's empire -- Apostle of Christ -- Alternative voices -- Imagining a future for the Bible.
Includes bibliographical references (p. 223-230) and indexes.
Keywords: Bible -- Introductions; Liberalism -- Religious aspects -- Christianity